Boosting English Motivation and Writing Proficiency through Instagram Captions in Discovery-Based Learning - Novikaya Putri; Andang Saehu; Bachtiar (Universitas Sulawesi Barat, 2025)
This study explores the impact of integrating Instagram captions within the Discovery-Based Learning framework on enhancing writing skills and student motivation. Grounded in the principles of student-centered learning, the research aims to address challenges in writing proficiency and motivation among tenth-grade students at SMKN 2 Rejang Lebong, Indonesia. A quasi-experimental design with a non-equivalent control group was employed, where the experimental group engaged in Instagram-based writing activities, including caption creation and peer feedback. In contrast, the control group followed traditional teaching methods. Data were collected through pre-tests and post-tests to assess writing skills, complemented by a motivation questionnaire. The results revealed a significant improvement in the experimental group’s writing skills, particularly in vocabulary, sentence structure, and coherence. Moreover, the experimental group demonstrated a marked increase in motivation, indicating that Instagram captions effectively engage students. The findings highlight the potential of leveraging social media platforms like Instagram to enhance language learning, providing a more interactive and student-centered approach. This study underscores the importance of integrating technology into educational practices to foster greater student engagement and motivation. The results suggest that when used within the Discovery Learning model, Instagram can significantly improve writing proficiency and intrinsic motivation, offering a modern, engaging method for enhancing learning outcomes. Future research could investigate the long-term effects of such interventions and explore additional digital tools to support student development in writing skills further.